Effect of Nitrogen and Variety on Quality Performance of Rhodes Grass (Chloris gayana Kunth) in the Sudan (Global Journal of Science Frontier Research, 2020)
An experiment was conducted in Shambat (2016)(2017) in the demonstration farm of the College of Agricultural Studies, Sudan University of Science and Technology to study the effect of variety and nitrogen fertilization on the quality performance of Rhodes grass. Two Rhodess grass varieties (Fine Cut and Reclaimer) and three nitrogen levels (60kgN/ha, 120kg N/ha and Control= 0.0kgN/ha) were investigated across seven cuts. The treatments were studied as factorial arrangement in Completely Randomized Design. Proximate analysis for Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF) and Crude Protein(CP) was carried out.
Keywords: NDF; ADF; CP; cutting age